Organização do trabalho e a mobilização subjetiva de trabalhadores de um centro de atenção psicossocial, álcool e drogas - Machado, Katiusci Lehnhard (2015)
This study aimed to understand how the organization of work affects the subjective mobilization of workers of a Psychosocial Care Center, Alcohol and Drugs in a municipality in the central region of the state of Rio Grande do Sul, Brazil. Qualitative research, which was used psychodynamics of work and developed from the work psychodynamics Clinic second application of medical devices and conditions for your driving. Four group sessions were held with sixteen fundamental level workers, middle and top of a Psychosocial Care Center Alcohol and Drugs in the period April-May 2014. In interpreting the findings used the Content Analysis. The results were organized into three areas: work organization, mobilization and subjective suffering, defenses and pathology and discussed based on the work psychodynamics. It was found that on an organization's bureaucratic and disinterested work by personal history, professional and the desire of workers, have created coping strategies, such as investing in training and support each other. Use your practical intelligence to protect themselves from suffering and organizational inflexibility resistance strategies. The discussion spaces help to reduce anxiety, ease and support worker strain. Cooperation, which translates into solid relationships, it is essential to work in a Psychosocial Care Center. Through it obtains experiences of pleasure; but also was established as work rule and became rigid and exclusive. Workers do not feel valued and supported by superiors in ways that give meaning to their work. This produces implications the construction of identity and engagement activity they perform. Use defensive strategies in situations where they do not get recognition. We conclude that there is a lack of analysis of space on the work, which leads workers to deny reality. The use of practical intelligence, cooperation and discussion space to reframe the suffering experience, has not been enough to turn it into pleasure. Thus, defense strategies have overlapped subjective mobilization.